2021
DOI: 10.3390/d13020053
|View full text |Cite
|
Sign up to set email alerts
|

Digging Deeper into the Ecology of Subterranean Ants: Diversity and Niche Partitioning across Two Continents

Abstract: Soil fauna is generally understudied compared to above-ground arthropods, and ants are no exception. Here, we compared a primary and a secondary forest each on two continents using four different sampling methods. Winkler sampling, pitfalls, and four types of above- and below-ground baits (dead, crushed insects; melezitose; living termites; living mealworms/grasshoppers) were applied on four plots (4 × 4 grid points) on each site. Although less diverse than Winkler samples and pitfalls, subterranean baits prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Although we did not specifically evaluate this hypothesis in our study because of uncertainty regarding the fossils, two previous works are available that have tested the pattern using ancestral state reconstruction across extant ants (Lucky et al ., 2013; Nelson et al ., 2018), which we will discuss in combination with the next hypotheses due to their continuity of explanation. Notably, Houadria & Menzel (2021) recently found that subterranean (hypogaeic) ants, even those which may forage above ground, were more specialized in their diet relative to epigaeic species.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not specifically evaluate this hypothesis in our study because of uncertainty regarding the fossils, two previous works are available that have tested the pattern using ancestral state reconstruction across extant ants (Lucky et al ., 2013; Nelson et al ., 2018), which we will discuss in combination with the next hypotheses due to their continuity of explanation. Notably, Houadria & Menzel (2021) recently found that subterranean (hypogaeic) ants, even those which may forage above ground, were more specialized in their diet relative to epigaeic species.…”
Section: Discussionmentioning
confidence: 99%
“…Two papers in the Special Issue address the structure and dynamics of ant communities. The first [7] uses a wide range of sampling methods, incorporating diverse food resources along with sampling in different vertical strata, to examine niche partitioning in rainforest ant communities of French Guiana and Borneo. Many cryptobiotic species were recorded primarily or exclusively at subterranean baits, which supports findings from several recent studies (including [3]) that a diverse fauna of highly specialized hypogaeic species is characteristic of the tropics.…”
mentioning
confidence: 99%